The Role of Categorical Perception and Acoustic Details in the Processing of Mandarin Tonal Alternations in Contexts: An Eye-Tracking Study - Tu, Jung-Yueh; Chien, Yu-Fu (Frontiers in Psychology, 2022)
This study investigated the perception of Mandarin tonal alternations in disyllabic words. In Mandarin, a low-dipping Tone3 is converted to a high-rising Tone2 when followed by another Tone3, known as third tone sandhi. Although previous studies showed statistically significant differences in F0 between a high-rising Sandhi-Tone3 (T3) and a Tone2, native Mandarin listeners failed to correctly categorize these two tones in perception tasks (Peng, 2000). The current study utilized the visual-world paradigm in eye-tracking to further examine whether acoustic details in lexical tone aid lexical access in Mandarin. Results showed that Mandarin listeners tend to process Tone2 as Tone2 whereas they tend to first process Sandhi-T3 as both Tone3 and Tone2, then later detect the acoustic differences between the two tones revealed by the sandhi context, and finally activate the target word during lexical access. The eye-tracking results suggest that subtle acoustic details of F0 may facilitate lexical access in automatic fashion in a tone language.